(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article describes the self-guided (individual) work methods of students in foreign language learning, its types and forms. The problems of self-guided work have been analyzed. The key components of influence on improvement of efficiency in professional training of graduates have been discovered.